Strain Sensing with Metamaterial Composites. Issue 9 (18th February 2019) - Everitt, Henry O.; Tyler, Talmage; Caraway, Bill D.; Bingham, Chris M.; Llopis, Antonio; Heimbeck, Martin S.; Padilla, Willie J.; Smith, David R.; Jokerst, Nan M.
Abstract: Mapping strain fields in visually opaque structural composites—for which failure is often sudden, irreparable, and even catastrophic—requires techniques to locate and record regions of stress, fatigue, and incipient failure. Many composite materials are transparent in the terahertz spectral region, but their strain history is often too subtle to recover. Here, terahertz metamaterials with strain‐severable junctions are introduced that can identify structurally compromised regions of composite materials. Specifically, multilayer arrays of aluminum meta‐atoms are designed and fabricated as strip dipole antennas with a terahertz frequency resonance and a strong response to cross‐polarized radiation that disappears when local stress irreversibly breaks their bowtie‐shaped junction. By spatially mapping the local polarimetric response of this metamaterial as a function of global strain, the regions of local stress extrema experienced by a visually opaque material may be visualized. This proof‐of‐concept demonstration heralds the opportunity for embedding metamaterial laminates within composites to record and recover their strain‐dependent history of fatigue. Abstract : A new concept for mapping strain fields in composite materials is introduced, using a specially tailored metamaterial composed of multilayer arrays of severable strip dipole antennas. Because their terahertz resonance and strong response to cross‐polarized radiation disappears when local stress irreversibly breaks the bowtie junction, the occurrence of local stress above a predetermined threshold may be permanently recorded and recovered.